Oral Breathing Effects on Malocclusions and Mandibular Posture: Complex Consequences on Dentofacial Development in Pediatric Orthodontics - Dana Feștilă; Cristina Dora Ciobotaru; Tudor Suciu; Cristian Doru Olteanu; Mircea Ghergie (Children)
Background/Objectives: Oral breathing is a common condition, particularly in children, and it is associated with significant changes in craniofacial development, dentomaxillary anomalies, and overall health. Despite extensive research, the role of oral breathing in the development of malocclusion remains controversial, with debates on whether it is a causative factor or a secondary adaptation to existing craniofacial issues. Methods: This narrative review synthesizes studies published in the last 15 years, focusing on the impact of oral breathing on dentofacial development and mandibular posture. A comprehensive search was conducted on four electronic databases (Embase, Medline, ProQUEST, Scopus) using keywords related to oral breathing, malocclusion, mandibular posture, and craniofacial development. Studies were included if they focused on the effects of oral breathing on craniofacial morphology, malocclusion, and postural changes in children and adolescents aged 6–18 years. Results: Results indicate a strong link between oral breathing and dentofacial changes such as adenoid facies, Class II malocclusion, posterior crossbite, and anterior open bite. It causes cranial posture changes, particularly increased craniocervical extension, as a compensatory mechanism to maintain airway patency. Conclusions: Oral breathing is a risk factor for malocclusion prognosis, especially in growing children. Dentofacial changes in oral breathers include adenoid facies, convex facial profile, and increased lower facial height. Oral breathing also leads to significant changes in cranial posture, often accompanied by mandibular, lingual, and palatal alterations.